PERGESERAN NILAI ADAT DAN BUDAYA DALAM PERKAWINAN MASYARAKAT GORONTALO DI MASA PANDEMI COVID-19 - Jibu, Supriyanto Agus; Kustiawan, Muhamad Taufik (Ahkam: Jurnal Hukum Islam, 2021)
This research was conducted to find out for how the shifting of marriage customs values ​​that occurred in Gorontalo during the Covid-19 Pandemic. This research will provides an information on the factors causing the shift in the tradition of traditional marriage values ​​in Gorontalo. This research uses qualitative methods and uses data collection techniques carried out by observation and interviews. The results of this study can be concluded that the marriage customs during the Covid-19 Pandemic that occurred in the Gorontalo community experienced a shift, time and form of presentation. This is also due to modernization which presents a new transformation in the implementation of traditional marriage in Gorontalo. Apart from the factor of the Covid-19 which affects changes in traditional customs and culture, there are also other causes, such as; economic factors, the factors of progress contaminated by art, new cultures, and the dynamics of interpretation of religious understanding.